2022
DOI: 10.1007/s40291-022-00627-w
|View full text |Cite
|
Sign up to set email alerts
|

Candidate MicroRNA Biomarkers in Lupus Nephritis: A Meta-analysis of Profiling Studies in Kidney, Blood and Urine Samples

Abstract: Lupus nephritis (LN) is a kidney disease caused by systemic lupus erythematosus in which kidneys are attacked by the immune system. MiRNAs participate in the pathogenesis of LN as modulatory effectors in immune responses and nephrogenesis pathways. Despite the large number of miRNAs that are expressed deferentially, identifying the most suitable biomarker candidate for LN is challenging. The aim of this study was to introduce a consensus panel of potential miRNA biomarkers by performing a meta-analysis of miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…However, recent statistical approaches have made it possible to combine miRNA profiling studies from different platforms without raw data and generalized normalization using RRA [ 20 , 73 ] and the vote-counting method [ 21 ]. These approaches have been successfully validated in previous studies in kidney diseases [ 13 , 15 , 17 ] and heart failure [ 22 ]. Our meta-analysis summarizes hypothesis-free miRNA profiling studies of CKDs by etiology, biological samples, and stages that might reveal novel miRNAs and avoid miRNA selection bias from the investigator side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent statistical approaches have made it possible to combine miRNA profiling studies from different platforms without raw data and generalized normalization using RRA [ 20 , 73 ] and the vote-counting method [ 21 ]. These approaches have been successfully validated in previous studies in kidney diseases [ 13 , 15 , 17 ] and heart failure [ 22 ]. Our meta-analysis summarizes hypothesis-free miRNA profiling studies of CKDs by etiology, biological samples, and stages that might reveal novel miRNAs and avoid miRNA selection bias from the investigator side.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified dysregulation of miRNA in various types of kidney diseases in mice [ 10 , 13 ] and humans [ 14 , 15 , 16 , 17 ], suggesting their use as potential biomarkers for diagnosis [ 18 ] and as nucleic acid therapy [ 19 ]. Therefore, it is crucial to understand the miRNA expression patterns in various sample types during specific disease stages and their functional role in the development and progression of CKD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several miRNAs serve as potential disease biomarkers for LN. Epigenetic studies regarding SLE have highlighted a set of urinary miRNAs, including miR-146a, miR-204, miR-30c, miR-3201, and miR-1273e, that are associated with LN [125]. These miRNAs play roles in LN-specific pathways, such as nucleic acid processes and inflammation, as well as in kidney function regulation through WNT and TGF-β signaling.…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Among epigenetic alterations reported in SLE, a list of 5 urinary miRNAs (miR-146a, miR-204, miR-30c, miR-3201, miR-1273e) present in extracellular vesicles have been associated with LN in a meta-analysis from 11 LN studies [127]. These miRNAs are associated with LN-related pathways (e.g., RNA/DNA nucleic acid and inflammatory pathways) and renal homeostasis (e.g., WNT and TGF-beta signaling).…”
Section: Mi-rnasmentioning
confidence: 99%